Legal Protection of Copyright Holders in Remix and Mashup Work Commercialized on Social Media - Damayanti, Miranda; Alamanda, Asri Elies; Mangar, Irma (Journal of Development Research, 2025)
The development of digital technology and social media has allowed the creation of remixes and mashups that are increasingly popular, but often have the potential to infringe copyright. Many remixes and mashups are commercialized without permission from the original copyright holders, causing problems in the protection of rights to the work. This research is important to provide a deeper understanding of the challenges and solutions of copyright protection in cyberspace, especially related to works that are traded on social media platforms. Remixes of songs carried out by content creators by changing the tempo of the song and the tone of the singer's voice are done without the permission of the creator and/or copyright holders. The purpose of this study is to analyze the form of copyright infringement that occurs in remix and mashup works that are commercialized on social media. The method used is a qualitative approach with case studies, collecting data through literature studies and juridical analysis of the laws and regulations that regulate copyright in Indonesia and related international regulations. The research also involved interviews with legal experts and social media practitioners to gain practical perspectives on the implementation of copyright protection. It is hoped that the results of this research can contribute to optimizing legal protection for copyright holders of remix and mashup works commercialized on social media.